Uganda : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2010)
Uganda's National Development Plan (NDP) stipulates medium-term strategic direction, development priorities, and implementation strategies. It also details Uganda's current development status, challenges, and opportunities. The contribution of this NDP to the socioeconomic transformation will be demonstrated by improved employment levels, higher per capita income, improved labor force distribution in line with sectoral GDP shares, substantially improved human development and gender equality indicators, and the country's competitiveness position, among others. The impressive GDP growth performance has contributed to a significant reduction in poverty levels.